2007
DOI: 10.1152/ajpheart.00424.2007
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II attenuates myocardial interstitial acetylcholine release in response to vagal stimulation

Abstract: exerts a variety of effects on the cardiovascular system, its effects on the peripheral parasympathetic neurotransmission have only been evaluated by changes in heart rate (an effect on the sinus node). To elucidate the effect of ANG II on the parasympathetic neurotransmission in the left ventricle, we measured myocardial interstitial ACh release in response to vagal stimulation (1 ms, 10 V, 20 Hz) using cardiac microdialysis in anesthetized cats. In a control group (n ϭ 6), vagal stimulation increased the ACh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Although it is generally accepted that the vagus nerve innervates only the sino-atrial node and atrioventricular node in the heart, Kakinuma et al demonstrated that acetylcholine released from vagal stimulation had a protective effect on ischemic myocardium in rats (32), suggesting that acetylcholine may diffuse throughout the left ventricle. Studies also showed that vagal stimulation increased the acetylcholine levels in the left ventricle in rats (33) and acetylcholinesterase-positive nerves were found to be distributed in the ventricle of human hearts (34), indicating that acetylcholine from the vagus nerve was able to act on myocardial cells in the left ventricle. Thus it seems possible that vagus nerve function may influence expression of α7nAChR of myocardial cells in the left ventricle through acetylcholine.…”
Section: Discussionmentioning
confidence: 96%
“…Although it is generally accepted that the vagus nerve innervates only the sino-atrial node and atrioventricular node in the heart, Kakinuma et al demonstrated that acetylcholine released from vagal stimulation had a protective effect on ischemic myocardium in rats (32), suggesting that acetylcholine may diffuse throughout the left ventricle. Studies also showed that vagal stimulation increased the acetylcholine levels in the left ventricle in rats (33) and acetylcholinesterase-positive nerves were found to be distributed in the ventricle of human hearts (34), indicating that acetylcholine from the vagus nerve was able to act on myocardial cells in the left ventricle. Thus it seems possible that vagus nerve function may influence expression of α7nAChR of myocardial cells in the left ventricle through acetylcholine.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, it has been demonstrated that administration of angiotensin II by intravenous route inhibited the bradycardia induced by vagal stimulation [54,55]. Kawada et al [56] demonstrated that angiotensin II may mediate these effects by decreasing the release of acetylcholine in response to vagal stimulation.…”
Section: Modulators Of Parasympathetic Functionmentioning
confidence: 99%
“…Kawada T et al [19] reported that intravenous injection of Ang II reduced vagal nerve stimulation-induced ACh release in the left ventricle, an effect that can be abolished by the Ang II antagonist losartan. These results imply that the beneficial effects of ACE inhibitors and AT1 receptor antagonists for CVD may include not only sympathetic activity suppression, but also an enhanced vagal activity in the ventricle.…”
Section: Introductionmentioning
confidence: 99%